Can internet use change sport participation behavior among residents? Evidence from the 2017 Chinese General Social Survey - Zhong, Hua-mei; Xu, Han-bing; Guo, En-kai; Li, Jing; Wang, Zhao-hong (Frontiers in Public Health, 2022)
Purpose: The popularisation of the internet has promoted the implementation of China's national fitness strategy and created conditions for Chinese residents to participate in sports. The internet is an essential medium for disseminating sports knowledge, and the use of the internet can change sports participation behaviours. Therefore, the internet can be used to popularise sports knowledge and promote the participation of all people in sports and thus improve the health of the whole population. This study attempted to empirically analyse how the use of the internet changes sports participation behaviour. Method: Utilising data from the 2017 China General Social Survey, a probit model, ivprobit model, and bias-corrected nonparametric percentile bootstrap test were used to analyse the impact of internet use on sports participation behaviour. Results: The empirical results show that internet use significantly increased the probability of participation in sports by Chinese residents. Heterogeneity test results showed that internet use was more effective in promoting sports participation in middle-aged groups, groups of older persons, unmarried groups, and groups with a high school education or above. The mediating effect test results show that internet use influences residents' participation in sports by promoting social interaction, leisure and entertainment, and learning and recharging. Conclusions: The internet has indeed changed participation in sports such that the use of the internet promotes it. Additionally, internet use has a more obvious impact on improving the sports participation behaviour of middle-aged groups, groups of older persons, unmarried groups, and middle and higher education groups. Internet social interaction, internet entertainment and internet learning are effective channels to encourage Chinese residents to participate in sports and improve their health.